Phylogenetisch-systematische Revision des Genus Temnorhynchus Hope, 1837 (Coleoptera: Scarabaeoidea: Melolonthidae: Dynastinae: Pentodontini). 1. Teil: Phylogenetische Analyse, mit Anmerkungen zur phylogenetisch-systematischen Methodologie. - Krell, Frank-Thorsten (Contributions to Entomology = Beiträge zur Entomologie, 1993)
For the phylogenetic analysis of the afrotropical/east-mediterranean genus Temnorhynchus Hope, 1837 (Insecta: Coleoptera: Scarabaeoidea: Melolonthidae: Dynastinae: Pentodontini) the ecological-adaptive and organismic relations of some structures of the head, especially the lamina epicranialis, the mouth parts, the pronotum, the legs, the alae, the aedoeagus, the surface sculpture and the colouration are discussed. The value of these definable characters for phylogenetic systematics is mostly poor. On this basis the phylogenetic system is not completely recognizable. The hypothetic phylogenetic system of Temnorhynchus is elaborated and shown in argumentation diagrams (cladograms). The genus consists of two monophyla, i.e. the subgenus Temnorrhynchodes Prell (six Madagascan species plus T. retusus and T. scutiger) and the subgenus Temnorhynchus s. str. (18 species), and of two species sedis incertae, i.e. T. grandicornis Fairmaire and T. cribratus Bates. The former genus Neotemnorrhynchus Janssens, 1949, is a junior synonym of Temnorhynchus Hope. The genus group (Dipelicus Hope + Lonchotus Arrow + Ampotis Dechambre & Madge) is postulated as the adelphotaxon (sister group) of Temnorhynchus. Besides morphology, the chorology, biogeography, autecology, and phenology of the taxa are studied. The Temnorhynchus species seem to prefer sandy soil with high grasses such as sugar cane. The morphology of the head and the legs shows typical adaptations to sand-burrowing habits. The record of the damage of T. coronatus (’sansibaricus’) to cocos palms is refuted. Keywords Coleoptera, Scarabaeoidea, Melolonthidae, Dynastinae, Temnorhynchus Hope, Neotemnorrhynchus Janssens syn. nov., revision, phylogenetic analysis, theory of phylogenetic systematics, chorology, biogeography, ecological-adaptive relations, organismic relations. Nomenclatural Acts Neotemnorrhynchus Janssens, 1949 (Melolonthidae), syn. n. of Temnorrhynchus Hope, 1837